1985
DOI: 10.1128/iai.47.3.638-647.1985
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and immunobiological properties of lipopolysaccharide (LPS) from Bacteroides gingivalis and comparison with LPS from Escherichia coli

Abstract: Lipopolysaccharides (LPSs) were isolated from Bacteroides gingivalis and Escherichia coli by the phenolwater and butanol-water procedures. The phenol-water-extracted LPS from B. gingivalis 381 was composed of 46% carbohydrate, 23% hexosamine, 18% fatty acid, and 5% protein. The major component sugars of this preparation were glucose, glucosamine, rhamnose, galactose, galactosamine, and mannose, and their molecular ratio was 1:0.9:0.7:0.6:0.6:0.4, respectively. Neither heptose nor 2-keto-3-deoxyoctonate was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
1
3

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(88 citation statements)
references
References 27 publications
(27 reference statements)
5
79
1
3
Order By: Relevance
“…Similar preparations were obtained from whole cells of E. eoli K235 by the phenolwater and butanol-water extractions and were designated as E. eoli LPS and LPG, respectively. The chemical composition and immunobiological activities of the E. coli preparations were reported recently by Koga et al (1985). These preparations were used in this study for comparison with those o[ A. actinomycetemcomitans.…”
Section: Extraction and Isolation Of Lps And Lpgmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar preparations were obtained from whole cells of E. eoli K235 by the phenolwater and butanol-water extractions and were designated as E. eoli LPS and LPG, respectively. The chemical composition and immunobiological activities of the E. coli preparations were reported recently by Koga et al (1985). These preparations were used in this study for comparison with those o[ A. actinomycetemcomitans.…”
Section: Extraction and Isolation Of Lps And Lpgmentioning
confidence: 97%
“…The crude extract was treated with nuclease, washed extensively with pyrogen-free water by ultracentrifugation, and lyophilized. Furthermore, LPG was prepared from whole cells by the butanolwater extraction method as described previously by Koga et al (1985). These extracts were not treated with proteolytic enzymes.…”
Section: Extraction and Isolation Of Lps And Lpgmentioning
confidence: 99%
“…(ii) They suggested that the classic LPS inhibitor polymyxin B prevented the adherence induced by the enterobacterial LPS but not the adherence by leptospires. However, the mitogenicity for spleen cells was unaffected by polymyxin B when Porphyromonas gingivalis LPS (18) or leptospire LPS (unpublished data) was used. (iii) They described that a total lipid extract gave negative results.…”
mentioning
confidence: 96%
“…LPS was extracted from lyophilized cells of A. actinomyceiemcomilans by the hot phenol-water procedure of Westphal & Jann (19). The crude extract was treated with nuclease, washed extensively with pyrogen-free water by ultracentrifugation, and lyophilized (20). These materials from A. actinomyceiemcomilans strains ATCC 29523, Y4 and NCTC 9710 are referred to as ATCC 29523 LPS, Y4 LPS, NCTC 9710 LPS, respectively.…”
Section: Preparations Of Lps and Lipid Amentioning
confidence: 99%
“…Murine spleen cells from C3H/HeN and C3H/HeJ mice were suspended in RPMI 1640 medium (GIB-CO Laboratories, Grand Island, NY) supplemented with penicillin (100 U/ml), streptomycin (100 g/ml), and A'-2-hydroxyethyl-piperazine-A''-2cthanesulfonic acid (HEPES) buffer (pH 7.2, 15 mM), and adjusted to 5 x lO'/ml. Spleen cells (5 x 10^) were culturd in triplicate in a 96-well microculture plate in a total volume of 0.2 ml ofthe medium containing various amounts of LPS, hpid A or concanavalin A (ConA; Sigma) at 37 °C in a humidified 5% COj atmosphere (20). Cultures were pulsed with 0.25 fiG of ['HJthymidine (['H]TdR; 2 Ci/mmol; ICN Radiochemicals, Irvine, CA) during the final 6 h of a 48-h incubation.…”
Section: Milogenic Activitymentioning
confidence: 99%